Isolated groups of extremely blue dwarf galaxies. Issue Volume 15:Issue S359(2020) (March 2019) - Bootz, Vitor; Trevisan, Marina; Thuan, Trinh; Izotov, Yuri; Krabbe, Angela; Dors, Oli
Abstract: Interactions and mergers between dwarf galaxies are mostly gas-rich and should be marked by an intense star formation activity. But these processes, which are expected to be common at earlier times, are very difficult to observe at low redshifts. To investigate that, we look in the Sloan Digital Sky Survey (SDSS) for compact groups that contain one luminous compact galaxy (LCG) with very high specific star formation rate (sSFR) and at least two other blue galaxies. We found 24 groups that satisfy these criteria, among which 12 groups have SDSS spectroscopic data for at least 2 member galaxies. Here we want to investigate, using the tidal strength estimator Q, how interactions between neighbouring galaxies affect the sSFR and concentration of each LCG. Statistical tests reveal a correlation between Q and their sSFR, indicating that tidal forces between neighbouring galaxies might be inducing bursts of star formation in the LCGs.